Low-Profile Wideband Solar-Cell-Integrated Circularly Polarized CubeSat Antenna for the Internet of Space Things - Wang, Heesu; Park, Yong Bae; Park, Ikmo (IEEE Access, 2022)
This paper proposes a low-profile wideband circularly polarized (CP) antenna using solar cell patches as radiation elements and a sequentially rotated feeding network for CubeSat applications. To realize a wide axial ratio (AR) bandwidth with a compact size, a sequentially rotated feeding network was designed by modifying a quadrature hybrid coupler and a rat-race coupler that has a small change in phase difference even when the frequency changes. A wideband CP patch array antenna was designed by combining a C-shaped slot-coupled solar cell patch in conjunction with a novel feeding network. The overall size of the proposed CP CubeSat antenna is 100 × 100×7.2 mm3 (0.83 λo × 0.83 λo × 0.06 λo at 2.5 GHz). Solar cells occupy 79% of the antenna area, enabling efficient energy harvesting. The -10 dB impedance bandwidth is 1.98-3.0 GHz, which is a fractional bandwidth of approximately 41.0%. The 3-dB AR and 3-dB gain bandwidths are 1.98-3.0 GHz (41.0%) and 1.82-2.98 GHz (46.6%), respectively. The proposed CP solar patch array antenna demonstrates a constant radiation pattern within the -10 dB impedance bandwidth. The proposed CubeSat antenna is suitable for use in an Internet of Space Things (IoST) autonomous communication system.
Keywords: Antenna feeds; Antennas radiation patterns; Circularly polarized antennas; Cubesat; Cubesat antenna; Hybrid coupler; Integrated antennas; Internet of space thing; S-band antenna; Sequentially rotated antenna; Solar cell integrated antenna; Circularly polarized antenna; CubeSat antenna; hybrid coupler; Internet of Space Things; S-band antenna; sequentially rotated antenna; solar cell integrated antenna